2018
DOI: 10.1155/2018/2360430
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Temperature-Humidity Index and Dorsal Fat Thickness during the Last Trimester of Gestation and Early Postpartum Period Affect Fertility ofBos indicusCows in the Tropics

Abstract: In order to measure the influence of the temperature-humidity index (THI) and the variation of fat thickness on reproductive performance, ninety-two Bos indicus cows kept under grazing conditions were used in two farms in Veracruz (Mexico) and Puntarenas (Costa Rica). THI was calculated with the average environmental temperature and relative humidity. Measurements of fat thickness (FAT) were taken two weeks apart from the last trimester of gestation to approximately 80 days postpartum (dpp). Natural breeding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, in further experiments, Díaz et al [60] found that animals with adequate metabolic conditions during the latter part of gestation have a better chance of pregnancy regardless of the time postpartum when the reproductive program starts. Comparing two locations in the dry tropics of Mexico and Costa Rica, Díaz et al [61] found a different pattern in body weight equilibrium prior to and after calving but a common feature for stability was the adaptability to variations in the temperature humidity index. Jolly et al [62] in Australia concluded that low body condition score at calving was associated with prolonged postpartum anestrus.…”
Section: Weaning Methodsmentioning
confidence: 99%
“…Moreover, in further experiments, Díaz et al [60] found that animals with adequate metabolic conditions during the latter part of gestation have a better chance of pregnancy regardless of the time postpartum when the reproductive program starts. Comparing two locations in the dry tropics of Mexico and Costa Rica, Díaz et al [61] found a different pattern in body weight equilibrium prior to and after calving but a common feature for stability was the adaptability to variations in the temperature humidity index. Jolly et al [62] in Australia concluded that low body condition score at calving was associated with prolonged postpartum anestrus.…”
Section: Weaning Methodsmentioning
confidence: 99%
“…Because of these shortcomings, the pharmacological control of estrus is emerging as an alternative [ 98 ]. However, despite an array of protocols to synchronize estrus and ovulation, and the use of fixed-time artificial insemination, THI, and the season, either wet or dry, can directly affect the reproductive performance of dual-purpose cattle [ 99 , 100 ]. Additionally, there is a marked difference when applying a pharmacological approach to heifers [ 101 ] compared with postpartum cows, as the latter will be influenced by the presence of the calf, either via suckling, or via the milk let down during lactation [ 102 , 103 ].…”
Section: Breeding Proceduresmentioning
confidence: 99%
“…Animals raised under pasture conditions depend on adequate fodder to gain weight after calving and have enough milk for their young [ 52 ]. This is not an easy feat considering that animals tend to calve in the spring, usually prior to the rainy season, where the fodder available in the last trimester of pregnancy could affect the onset of ovarian activity [ 56 , 57 ]. In effect, in a comparative study between two locations in the tropics of México and Costa Rica where the onset of the rainy season could vary, it was found that the pattern of body loss in the last trimester of gestation was directly related to the onset of the rainy season [ 58 ].…”
Section: Reproductive Performancementioning
confidence: 99%
“…In effect, in a comparative study between two locations in the tropics of México and Costa Rica where the onset of the rainy season could vary, it was found that the pattern of body loss in the last trimester of gestation was directly related to the onset of the rainy season [ 58 ]. In fact, in a further experiment, when two groups of cows with different postpartum periods were subjected to a synchronization program, monitoring body fat change via ultrasound, it was found that the driving force for a prompt restoration of ovarian activity and pregnancy were the changes in body reserves rather than the time postpartum [ 56 , 57 ]. These examples illustrate the need for farmers and technicians alike to join resources to avoid body loss during the last trimester of gestation catering for the wellbeing of the dam and later for their offspring.…”
Section: Reproductive Performancementioning
confidence: 99%